(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article discloses the procedure for accounting for liabilities in joint ventures based on international standards. It clarifies the distinctive aspects between specifically valued liabilities and contingent liabilities, their recognition, their treatment in financial accounting and accounting policies, and furthermore, how to account for other related information in the explanatory notes.